Application of Cell-Derived Extracellular Vesicles and Engineered Nanovesicles for Hair Growth: From Mechanisms to Therapeutics - Gangadaran, Prakash; Rajendran, Ramya Lakshmi; Kwack, Mi Hee; Jeyaraman, Madhan; Hong, Chae Moon; Sung, Young Kwan; Ahn, Byeong-Cheol (Frontiers in Cell and Developmental Biology, 2022)
Hair loss is one of the most common disorders that affect both male and female patients. Cell-derived nanovesicles (CDVs) are natural extracellular vesicles and engineered nanovesicles that can carry various biological materials such as proteins, lipids, mRNA, miRNA, and DNA. These vesicles can communicate with local or distant cells and are capable of delivering endogenous materials and exogenous drugs for regenerative therapies. Recent studies revealed that CDVs can serve as new treatment strategies for hair growth. Herein, we review current knowledge on the role of CDVs in applications to hair growth. The in-depth understanding of the mechanisms by which CDVs enable therapeutic effects for hair growth may accelerate successful clinical translation of these vesicles for treating hair loss.